2010
DOI: 10.1016/j.chemphys.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Subdiffusive Brownian ratchets rocked by a periodic force

Abstract: This work puts forward a generalization of the well-known rocking Markovian Brownian ratchets to the realm of antipersistent non-Markovian subdiffusion in viscoelastic media. A periodically forced subdiffusion in a parity-broken ratchet potential is considered within the non-Markovian generalized Langevin equation (GLE) description with a power-law memory kernel $\eta(t)\propto t^{-\alpha}$ ($0<\alpha<1$). It is shown that subdiffusive rectification currents, defined through the mean displacement and subveloci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 97 publications
1
55
1
Order By: Relevance
“…. , N. And we proceed to express the proposed model (17) in terms of dimensionless one [54,55]. The distance is scaled in units of L, the energy is scaled in units of E 0 = mL 2 , coupling force and external harmonic force in units of…”
Section: Coupled Fractional Brownian Motormentioning
confidence: 99%
See 1 more Smart Citation
“…. , N. And we proceed to express the proposed model (17) in terms of dimensionless one [54,55]. The distance is scaled in units of L, the energy is scaled in units of E 0 = mL 2 , coupling force and external harmonic force in units of…”
Section: Coupled Fractional Brownian Motormentioning
confidence: 99%
“…Thus, generalized Langevin equation (GLE) [48][49][50][51] and fractional Langevin equation (FLE) [38,52,53] were proposed to describe the motion behaviors of particles in various memorable mediums. Igor et al respectively studied the rocking Markovian ratchets [54] and fluctuating tilt ratchets [55] based on fractional subdiffusion in sticky viscoelastic medium characterized by a power law memory kernel, and found that subdiffusive current could flow in the counterintuitive direction upon a change of temperature or driving frequency. However, all of these literatures were mainly restricted to the study on dynamics of single particle.…”
Section: Introductionmentioning
confidence: 99%
“…Such viscoelastic subdiffusion has recently been found relevant also for transport in polymer networks [27,28], cytosol of biological cells [29] and akin crowded fluids [30]. The corresponding fluctuating tilt or rocking ratchets in viscoelastic media have recently been proposed and studied in [31,32] with a number of quite unexpected and surprising properties revealed. There is growing interest in the ratchet effect in glass-like environments [33].…”
Section: Introductionmentioning
confidence: 99%
“…When ω 2 0 = 0, the Eq. (2) describes the normal diffusion with the mean-square displacement (MSD) which satisfies x 2 (t) ∼ t. However, a situation that should not be neglected is that the classical theory of Brownian diffusion cannot explain the subdiffusion phenomenon with MSD which satisfies x 2 (t) ∼ t α , 0 < α < 1 [2,3]. In mathematical descriptions of the subdiffusion phenomenon, the fractional dynamical systems play very important roles.…”
mentioning
confidence: 99%